Correlations between macrophage polarization and osteoinduction of porous calcium phosphate ceramics. (February 2020) - Chen, Xuening; Wang, Menglu; Chen, Fuying; Wang, Jing; Li, Xiangfeng; Liang, Jie; Fan, Yujiang; Xiao, Yumei; Zhang, Xingdong
Abstract: The host immune response is critical for in situ osteogenesis, but correlations between local inflammatory reactions and biomaterial osteoinduction are still poorly understood. This study used a murine intramuscular implantation model to demonstrate that calcium phosphate ceramics with different phase compositions exhibited divergent osteoinductivities. The osteoinductive potential of each ceramic was closely associated with the immunomodulatory capacity of the material, and especially with the regulation of macrophage polarization and functional status. Biphasic calcium phosphate (BCP) ceramics with superior osteoinductive potential enhanced the fraction of CD206 + M2 macrophages, up-regulated expression of M2 phenotypic markers in vitro, and increased the ARG + M2 population in vivo. This suggested that BCP ceramics could ameliorate long-term inflammation and build a pro-osteogenic microenvironment. However, β-tricalcium phosphate (β-TCP) ceramics with no obvious osteoinductivity increased the fraction of CCR7 + M1 macrophages, promoted the secretion of M1 phenotypic markers in vitro, and maintained a high proportion of iNOS + M1 macrophages in vivo . It indicated that β-TCP ceramics could exacerbate inflammation and inhibit ectopic bone formation. Hydroxyapatite ceramics with an intermediate osteoinductivity exhibited a moderate amount of both M1 and M2 macrophages. These findings highlight the critical role of macrophage polarization in biomaterial-dependent osteoinduction, which not only deepens our understanding of osteoinductive mechanisms but also provides a strategy to design bone substitutes by endowing materials with the proper immunomodulatory abilities to achieve the desired clinic performance. Statement of Significance: Calcium phosphate (CaP) ceramics with osteoinductive capacities are able to induce ectopic bone formation in non-osseous sites. However, its underlying mechanism is largely unknown. Previous studies have demonstrated an indispensable role of macrophages in osteogenesis, inspiring us that local inflammatory reaction may affect material-dependent osteoinduction. This study indicated that CaP ceramics with different phase composition could present divergent osteoinductive capacities through modulating polarization and functional status of macrophages, as biphasic calcium phosphate with potent osteoinductivity ameliorated long-term inflammation and induced a healing-associated M2 phenotype to initiate bone formation. These findings not only get an insight into the mechanism of CaP-involved osteoinduction, but also help the design of tissue-inducing implants by endowing biomaterials with proper immunomodulatory ability. Graphical abstract: Image, graphical abstract